Quantitative susceptibility mapping using single-shot echo-planar imaging - Sun, Hongfu; Wilman, Alan H. (Magnetic resonance in medicine, 2015)
Purpose To perform quantitative susceptibility mapping (QSM) in negligible acquisition time and apply it to measuring iron‐rich subcortical gray matter. Methods Whole brain QSM was performed using single‐shot gradient echo‐planar imaging (EPI) in under 7 seconds on a standard 1.5 T system for imaging brain iron in subcortical gray matter. The method was compared to a standard 6‐minute gradient recalled echo (GRE) QSM acquisition in healthy subjects. Region‐of‐interest QSM measurements were compared between methods in six subcortical gray‐matter nuclei and two white matter territories. Results EPI‐QSM provided similar mean susceptibility values to standard GRE‐QSM in iron‐rich subcortical gray matter regions, while providing greater than 50‐fold scan time reduction. Blurring from the low spatial resolution and transverse relaxation decay of EPI affected edges but had negligible effect on whole subcortical nuclei measurements, which had a high correlation (R2 = 0.96) to estimated iron content. Conclusion EPI‐QSM can be performed in several seconds, which enables expansion of brain iron studies of subcortical gray matter to cases where time is limited and to existing MRI studies that already uses gradient echo EPI. Magn Reson Med 73:1932–1938, 2015. © 2014 Wiley Periodicals, Inc.